THEORETICAL PRINCIPLES OF REGIONAL DEVELOPMENT IN MODERN CONDITIONS - Dziundziuk V.B.; Cherniak М.Ye. (Pressing Problems of Public Administration, 2017)
The evolution and main modern approaches to the analysis of regional development and its essential characteristics are considered. It is proved that in the science and practice of public administration there is no single, common de nition for regional development. It is shown that the de nition of development and its directions is always geographically differentiated, and may change over time. It was established that in the 21st century, there was a deviation from economic determinism in de ning regional development, and today the concept of ‘development’ is considered in terms of the need to take into account social, environmental, political, cultural, and other factors. It has been revealed that the process of managing territorial development should be carried out by various stakeholders, and their relations should be based on partnership and dialogue.